1983
DOI: 10.1001/archinte.143.9.1694
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic regimens in essential hypertension. A comparison of hypokalemic effects, BP control, and cost

Abstract: Intolerable side effects and hypokalemia during thiazide treatment of hypertension frequently necessitate a change in diuretic regimen. The hypokalemic effects, effectiveness in controlling BP, and cost of several alternate diuretic regimens were evaluated. Prevalences of serum K+ values less than 3.5 mEq/L were as follows for the various regimens: hydrochlorothiazide, 50 mg daily, 11.0% (n = 500); chlorthalidone, 25 mg daily, 8.1% (n = 37); triamterene, 100 mg, plus hydrochlorothiazide, 50 mg daily, 5.3% (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The incidence of adverse events was lower in both of these groups than in patients who continued or stopped ramipril therapy. Analysis of biochemical laboratory parameters during the active-controlled treatment period or the withdrawal period showed that approximately 5% of patients in each group had potassium levels under 3.5 mmol/l, which is not unexpected with HCTZ-containing treatment regimens [31,32]. Few patients in either group exhibited potassium levels over 5.5 mmol/ (< 2%) or !…”
Section: Discussionmentioning
confidence: 70%
“…The incidence of adverse events was lower in both of these groups than in patients who continued or stopped ramipril therapy. Analysis of biochemical laboratory parameters during the active-controlled treatment period or the withdrawal period showed that approximately 5% of patients in each group had potassium levels under 3.5 mmol/l, which is not unexpected with HCTZ-containing treatment regimens [31,32]. Few patients in either group exhibited potassium levels over 5.5 mmol/ (< 2%) or !…”
Section: Discussionmentioning
confidence: 70%
“…The dose of HCTZ can be increased or the HCTZ could be replaced by 25 mg of the more potent thiazide‐like diuretic chlorthalidone. 19,20 With either intervention, the potassium level must be monitored and addition of a potassium‐sparing diuretic should be considered 30 …”
Section: Options For Strengthening the Diuretic Regimenmentioning
confidence: 99%
“…Unfortunately, studies assessing higher doses of amiloride are not likely to be performed. Similarly, the dose of triamterene included in triamterene/HCTZ combination pills (37.5/25 mg or 75/50 mg) are often inadequate to protect the serum potassium level 30 …”
Section: Potassium‐sparing Diureticsmentioning
confidence: 99%
“…[24] This lack of significant reduction in potassium levels may reflect the low-renin, volume-dependent nature of hypertension in Nigerians, which may alter K+ homeostasis in response to therapy in blacks[25] or the relatively higher salt/potassium intake of the subjects studied.…”
Section: Discussionmentioning
confidence: 99%